The Effect of Tax Literacy, Service Quality of Tax Employees, Financial Attitudes, and Tax Understanding on Taxpayer Compliance: Pengaruh Literasi Pajak, Kualitas Pelayanan Pegawai Pajak, Sikap Keuangan, Serta Pemahaman Perpajakan Terhadap Kepatuhan Wajib Pajak - Arifin, Siti Amatul Kharimah; Sriyono, Sriyono (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of tax literacy, service quality of tax employees, financial attitudes, and understanding of taxation on taxpayer compliance (Study on MSMEs in Sidoarjo Regency). This study uses quantitative methods with primary data as a data source. Location This research was conducted in MSMEs in Sidoarjo Regency. The population in this study are small and medium entrepreneurs in Sidoarjo district. As a district dubbed the City of MSMEs, Sidoarjo has around 878 types of MSMEs spread across 18 sub-districts in Sidoarjo district. In this study, the technique used in sampling is purposive sampling method. The number of samples determined in this study based on the sampling criteria above, a sample of 164 MSMEs was obtained. The data analysis technique used in this research is Structural Equation Modeling Partial Least Square (SEM-PLS). The results of this study indicate that tax literacy has a significant and positive effect on taxpayer compliance. The Quality of Tax Service Employees has a Significant and Positive Effect on Taxpayer Compliance. Financial Attitude Has Significant and Positive Effect on Taxpayer Compliance. Tax Understanding has a Significant and Positive Effect on Taxpayer Compliance.